The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2337/db14-1696
|View full text |Cite
|
Sign up to set email alerts
|

Legacy Effect of Foxo1 in Pancreatic Endocrine Progenitors on Adult β-Cell Mass and Function

Abstract: β-Cell dysfunction in diabetes results from abnormalities of insulin production, secretion, and cell number. These abnormalities may partly arise from altered developmental programming of β-cells. Foxo1 is important to maintain adult β-cells, but little is known about its role in pancreatic progenitor cells as determinants of future β-cell function. We addressed this question by generating an allelic series of somatic Foxo1 knockouts at different stages of pancreatic development in mice. Surprisingly, ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…We observed a similar metabolic phenotype in mice carrying an embryonic deletion of FoxO1 in the pancreas (16), as these mice displayed fasting hyperglycemia, age-dependent glucose intolerance, and compromised arginine-stimulated insulin secretion. The difference between the two models is the developmental stage at which FoxO1 is inactivated (␤ cell versus pancreatic progenitor) (17), and the presence of FoxO3a and FoxO4.…”
Section: Pan-pancreatic Ablation Of Foxo1 Foxo3a and Foxo4supporting
confidence: 56%
“…We observed a similar metabolic phenotype in mice carrying an embryonic deletion of FoxO1 in the pancreas (16), as these mice displayed fasting hyperglycemia, age-dependent glucose intolerance, and compromised arginine-stimulated insulin secretion. The difference between the two models is the developmental stage at which FoxO1 is inactivated (␤ cell versus pancreatic progenitor) (17), and the presence of FoxO3a and FoxO4.…”
Section: Pan-pancreatic Ablation Of Foxo1 Foxo3a and Foxo4supporting
confidence: 56%
“…At both time points, we observed a transient up-regulation of Foxo1 (6.9 fold at FMD, 5.3 fold at RF1d, *p<0.05 comparing to AL) and of a set of genes that have been previously identified as dual regulators for both fat-metabolism and fate-determination in mammalian cells (Cook et al, 2015; Haeusler et al, 2014; Johnson et al, 2004; Kim-Muller et al, 2014; Mu et al, 2006; Stanger, 2008; Talchai et al, 2012; Talchai and Accili, 2015; Tonne et al)(Figure 4A), in agreement with the metabolic changes found in mice receiving the FMD (Figure S1). We further examined whether the metabolic reprogramming caused by the FMD affects lineage determination in pancreatic islets.…”
Section: Resultsmentioning
confidence: 78%
“…Although these studies revealed the feasibility of deriving β-like cells from the intestine, critical barriers remain in developing these approaches into future regenerative therapies. FoxO1 plays a critical role in protecting β cells from cellular stress (Kitamura et al, 2005; Talchai et al, 2012b), and deletion or suppression of FoxO1 in pancreatic β cells could result in β cell failure (Talchai et al, 2012b; Talchai and Accili, 2015). Moreover, although NPM factors induce insulin + cells in the intestine, the induced cells appear to lack certain important β cell genes such as Nkx6.1 and exhibit reduced glucose responsiveness compared with pancreatic β cells (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%